Acute kidney injury as a presentation of primary renal diffuse large B-cell lymphoma in HIV. (April 2014) - Hughes, DJ; Fitzgerald, N; Sran, H; Konig, M; Moore-Moffatt, R; Webb, A; Gilleece, Y; Churchill, DR
We report a case of acute kidney injury due to primary renal diffuse large B-cell lymphoma, which developed after initiation of tenofovir-containing antiretroviral therapy in a 28-year-old HIV-positive man.